Analisis Literatur tentang Peran Generasi Muda dalam Pengembangan Agribisnis Modern - Tampe Tuah Malem Ginting; Arief Muhazir Insandi (CV. Truly Science Publishing, 2025)
Background: The low participation of young people presents a serious challenge in ensuring the sustainability of this sector. Many young individuals are reluctant to engage in agribusiness because they perceive it as unpromising, lacking prestige, and full of risks. Aim: This study aims to identify the strategic role of youth in the development of modern agribusiness, as well as to analyze the challenges and opportunities that can be leveraged to increase their participation in the sector. Methods: The study uses a literature review method by examining various scientific journals, government policies, and reports related to agribusiness and youth participation in the agricultural sector. This approach seeks to summarize relevant findings and provide a comprehensive conceptual understanding. Results: The results show that young people have significant potential to advance agribusiness through the use of digital technology, product innovation, and entrepreneurial spirit. However, the challenges they face include limited access to land, capital, training, and a lack of targeted policy support. Several government policies, such as Presidential Regulation No. 2 of 2022, have attempted to address these challenges through youth entrepreneurship programs in the agricultural sector. Conclusion: Young people can become key drivers of modern agribusiness transformation in Indonesia if supported by appropriate policies, access to resources, and a conducive entrepreneurial ecosystem. Collaborative efforts from various stakeholders are needed to create an inclusive space for participation, making agriculture an attractive, profitable, and sustainable sector for the nation's future.